Presentation: Research and pastoral care: divorce necessary or convenient symbiosis? - Allpanchis, Revista (2007)
Shortly after celebrating the forty years of Allpanchis Phuturinqa, it seems convenient and even necessary to take stock of the path traveled, an exercise of awareness similar to the one carried out years ago by Fr. Manuel Marzal S.J., a renowned anthropologist who was entrusted to make a review of Andean research after twenty years of our journal. On that occasion, Marzal already highlighted the need to recover studies on Andean religion "[...] due to a certain fidelity to the founding charism of the bishops of the southern Andean region who wanted to better understand Andean religion and culture in order to better carry out their pastoral work.